(untitled) (GUB Journal of Science and Engineering, 2018)
The fundamental order antisymmetric mode (A0-mode) Lamb wave based a quantitative acoustical imaging technique is proposed in this paper to classify the corroded region under coating film within the metallic structure. This method estimates versatility qualities of the zone of intrigue to some degree inhomogeneity differentiated to the encompassed materials. However, a converging region consisting of incident wave field and scattered wave field difficult to demonstrate from the observed signals. The proposed method focuses on reconstructing the image of the defect by calculating the shear strains. The shear strains deduced from the observed normal displacement of the specimen. A covariance matrix has been constructed using the shear strains and meaningful determinant values of the matrix reveal the overlapping region. As the beginning overlapping region developed at the edge of the defect, thus image of the defect can be reconstructed by this technique. This paper discussed the analytical approach of computing the incoming, outgoing, as well as the transmitting wave fields. Physical interpretation of the analytical prediction is explored via numerical simulations and acoustical observations. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 5(1), Dec 2018 P 37-44